1995
DOI: 10.1080/15326349508807353
|View full text |Cite
|
Sign up to set email alerts
|

A generalization of the matrix M/G/l paradigm for Markov chains with a tree structure

Abstract: In this paper, we generalize the theory of the M/G/1 paradigm to tree-like structures. There are two variables in the Markov chain, one of which takes values on the nodes of a d-ary tree. The other is an auxiliary variable, which takes one of m possible values. For this structure, the steady state probability depends on d matrices, G I , . . . , Gd which are solutions of a system of non-linear matrix equations. We also apply the theory to a multiple class last-come-firstserved queue in which no preemption is a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
36
0

Year Published

2000
2000
2013
2013

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(36 citation statements)
references
References 4 publications
0
36
0
Order By: Relevance
“…Matrices {G(k), 1 ≤ k ≤ K} are the minimal nonnegative solutions to the matrix equations (Takine, Sengupta, and Yeung [16]):…”
Section: Fundamental Periods and Busy Periodsmentioning
confidence: 99%
“…Matrices {G(k), 1 ≤ k ≤ K} are the minimal nonnegative solutions to the matrix equations (Takine, Sengupta, and Yeung [16]):…”
Section: Fundamental Periods and Busy Periodsmentioning
confidence: 99%
“…The key feature of our approach lies in reformulating the traditional three queue problem into a combined queue and stack problem. We show that the behavior of the reformulated problem can be captured by a Markov chain with a tree structured state space [16,20]. This Markov chain-that neither fits within the GI/M/1 or M/G/1 paradigm-is reduced to a binary treelike process [3,17], which is a special case of a tree structured QBD Markov chain [19].…”
Section: Introductionmentioning
confidence: 99%
“…Depending on the transitions allowed in such a tree-structured Markov chain, several classes have been identified: (a) M/G/1-type (Takine et al 1995), (b) GI/M/1-type (Yeung and Sengupta 1994), (c) QBD-type (Yeung and Alfa 1999) and (d) tree-like processes (Bini et al 2003), where the latter two classes were shown to be equivalent (Van Houdt and Blondia 2003). In each of these models the transitions fulfill a spacial homogeneity property, that is, the transition probability between two nodes depends only on the spacial relationship between the two nodes and not on their specific values.…”
mentioning
confidence: 99%